2023
DOI: 10.1126/sciadv.adg8876
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 inhibition enhances SHP2 inhibitor efficacy and is dependent upon RB function in malignant peripheral nerve sheath tumors

Jiawan Wang,
Ana Calizo,
Lindy Zhang
et al.

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are highly aggressive soft tissue sarcomas with limited treatment options, and new effective therapeutic strategies are desperately needed. We observe antiproliferative potency of genetic depletion of PTPN11 or pharmacological inhibition using the SHP2 inhibitor (SHP2i) TNO155. Our studies into the signaling response to SHP2i reveal that resistance to TNO155 is partially mediated by reduced RB function, and we therefore test the addition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Both the SHP2 inhibitor RMC4550 and the JAK2 inhibitor decreased RAS-GTP levels in myeloproliferative neoplasm cells, and their combined employment enhanced ERK inactivation and increased apoptosis 37 . CDK4/6 inhibitor increased the efficacy of SHP2 inhibitor TNO155 by enhancing RB activity, greater inhibited cell cycle and apoptosis inhibitory proteins, which resulted in deeper and more sustained anti-tumor activity in malignant peripheral nerve sheath tumor models 38 . Combining the SHP2 inhibitor SHP099 with a pan-ERBB inhibitor suppressed the growth of lung cancer with defective or mutated epigenetic regulator KMT2D 39 .…”
Section: Discussionmentioning
confidence: 98%
“…Both the SHP2 inhibitor RMC4550 and the JAK2 inhibitor decreased RAS-GTP levels in myeloproliferative neoplasm cells, and their combined employment enhanced ERK inactivation and increased apoptosis 37 . CDK4/6 inhibitor increased the efficacy of SHP2 inhibitor TNO155 by enhancing RB activity, greater inhibited cell cycle and apoptosis inhibitory proteins, which resulted in deeper and more sustained anti-tumor activity in malignant peripheral nerve sheath tumor models 38 . Combining the SHP2 inhibitor SHP099 with a pan-ERBB inhibitor suppressed the growth of lung cancer with defective or mutated epigenetic regulator KMT2D 39 .…”
Section: Discussionmentioning
confidence: 98%
“… 47 Recently, the src homology region 2 (SH2)-containing protein tyrosine phosphatase-2 (SHP2) has gained attention in its role in adaptive signaling driven by receptor tyrosine kinase activation and preclinical data in MPNST demonstrate therapeutic efficacy of combined inhibition of SHP2 and MEK 48 or cyclin-dependent kinase 4/6 (CDK4/6). 49 Additionally, there is a growing interesting in immunotherapeutic approaches in the treatment of MPNST, alone or in combination with molecularly targeted therapies, although no clinical trials have demonstrated overall benefits of immune checkpoint blockade (ICB) to date in MPNST. Novel approaches used in preclinical models that have shown efficacy include the combination of ICB with CDK4/6 and MEK inhibition 50 and the use of virus-based immunotherapy.…”
Section: Discussionmentioning
confidence: 99%